Consciousness and meaning selected essays - Loar, Brian (Oxford University Press, 2017)
One of the most important problems of modern philosophy concerns the place of subjectivity in a purely physical universe. Brian Loar was a major contributor to the discussion of this problem for over four decades. This volume brings together his most important and influential essays in the philosophy of language and of mind